Implementasi Kebijakan Perhitungan Pajak Penghasilan Youtuber Orang Pribadi Di Indonesia Dengan Norma Perhitungan Penghasilan - Liska Kamal; Manita Hidayati (Jurnal Ilmu Administrasi Publik, 2023)
Background: The phenomenon in this study is the increasing number o Indonesian people who become YouTubers. YouTuber is someone who makes videos to be uploaded to YouTube for all other YouTube users to see. The income earned by YouTubers for their videos should be subject to tax in accordance with applicable regulations. Purpose: The purpose of this study is to determine the implementation of the individual YouTuber income tax calculation policy in Indonesia with the net income calculation norms, along with the obstacles and efforts made by the DGT and tax offices in implementing the tax policy. Result: This research is a type of descriptive research in which the data are analyzed qualitatively. The results of this study indicate that the basis for imposition of YouTuber's income tax is PER- 17/PJ/2015 where the tax is calculated using the net income calculation norms. However, in its implementation there are still many YouTubers who do not understand the procedure for calculating taxes from income they earn from Google AdSense. As a result, YouTubers are not aware of their tax rights and obligations.